Exploring the perceptions of Kurdish EFL university students towards culture as the fifth language skill - Omar Fouad Ghafor (Universitas Syiah Kuala, 2020)
Culture has been defined and viewed in different ways. These differences are due to its involvement with various facets of human life. Some of these definitions and viewpoints are related to the process of teaching/learning a language and understanding the habits of the native speakers of the language. In this regard, many linguists consider it the fifth language skill alongside the other four traditional skills that help language learners to master the language better. This paper addresses this issue by exploring the perceptions of Kurdish EFL university students concerning the role of English culture in learning the language. The researcher attempts to achieve this aim by providing a theoretical background about culture and culture as the fifth language skill and utilizing a questionnaire to a sample of senior undergraduate students selected for this purpose. The findings of the study show that cultural awareness has an essential role in the process of English language learning. Hence, culture should always be integrated with the process because it is an inseparable part of language teaching/learning. Teaching culture is as crucial as teaching other aspects and skills of the language.